A Series of Exceptionally Robust Luminescent Coordination Polymers Based on a Bipyridyldicarboxylate Ligand and Rare‐Earth‐Metal Ions. Issue 36 (14th November 2013) - Li, Liangjun; Tang, Sifu; Lv, Xiaoxia; Cai, Jinjun; Wang, Chao; Zhao, Xuebo
Abstract: A series of three‐dimensional rare‐earth coordination polymers, [M2 (bpdc)3 (H2 O)4 ] (M = Y [1 ], Sm [2 ], Eu [3 ], Gd [4 ], Tb [5 ], Dy [6 ], Er [7 ], and Yb [8 ]) were synthesized by solvothermal reactions of 2, 2′‐bipyridine‐5, 5′‐dicarboxylate (bpdc) with corresponding metal salts. Single‐crystal and powder X‐ray diffraction analyses demonstrated that these coordination polymers are isostructural. The carboxyl groups of the bpdc ligand are coordinated to metal ions and the 2, 2′‐bipyridine moieties are left free due to the preferable affinity of rare‐earth metals for oxygen‐donor atoms. The adjacent eight‐coordinate MO8 cores show dicapped trigonal prismatic environments; they are interconnected by carboxyl groups and are further bridged through the bipyridyl linkers to give quite dense three‐dimensional networks. Photoluminescent studies at room temperature reveal intense red and green luminescent emissions for Eu III and Tb III analogues, respectively. Furthermore, it is noteworthy that bpdc shows an effective antenna effect in sensitizing emissions from Eu III and Tb III ions. Thermogravimetric analyses demonstrate that these coordination polymers exhibit exceptional thermal stability (decomposing at T > 580 °C under N2 for compound1 ). Water‐resistance measurements of these coordination polymers show excellent hydrothermal stability. Abstract : A series of isostructural coordination polymers based on rare‐earth‐metal ions and a bipyridyldicarboxylate ligand were synthesized and characterized. The photoluminescent properties, thermal stability, and water resistance of these coordination polymers were investigated.